Health Service Delivery Quality and Patient Satisfaction in Pediatric Emergency Department - Yasin Yıldız; Mehmet Kenan Kanburoğlu (Galenos Yayinevi, 2021)
Introduction:Pediatric emergency care units serve continuous labor to a large group of patients with variable complaints. Waiting time is the period from the admission to discharge of a patient and is one of the main determinants of patient satisfaction. We aimed to measure satisfaction levels of the patients and the factors influencing it with particular attention to waiting time.Methods:We conducted the study in a level 3 pediatric emergency care unit of Rize Governmental University Hospital. We measured the period from the admission to physical examination, laboratory and radiological investigation, emergency medication, prescription, and discharge. At the end of discharge, we measured the level of satisfaction with Likert scale questions.Results:From 2.041 patients admitted to the pediatric emergency care between 4th and 10th of March 2019, we surveyed 662 patients. The mean age was 76.2±63.5 (0-204) months with a female to male ratio of 320/342. Three hundred seventy patients (55.7%) were classified as green, 289 (43.9%) as yellow and 3 (0.4%) as red. The mean waiting time of all patients was 8.9±11.6 (0-94) minutes. Doctors' level of paying attention to the patient was the highest-rated parameter in the questionnaire whereas waiting time was the lowest.Conclusion:According to the results, the waiting time of patients in our pediatric emergency department is less than the previous national and international reports. On the other hand, the ratio of the patients hospitalized or referred to another hospital is too low, which puts forward the problem of "unneeded patient admission". Avoidable patient density together with inconvenient use of medical resources may lead to insufficient care of the patients in absolute urgent need and decrease patient satisfaction. In order to enhance the quality of care, we need to educate health professionals, design the physical conditions of the institution, establish a well-functioning triage system and put the waiting time of patients under a reasonable duration.